Identifying Transmission Opportunity through Transmission Power and Bit Rate for Improved VANET Efficiency - Wei, Low Jun; Lim, Joanne Mun-Yee (Mobile networks and applications, 2019)
With the development of vehicular industry and wireless communication technology, vehicular ad hoc network (VANET) has become a popular research field. However, timely dissemination of safety related information in VANET is always challenging due to the highly dynamic vehicular environment. In this paper, we investigate an analytic approach in enhancing transmission efficiency of VANET by adapting transmission power and bit rate for IEEE 802.11p based VANET. The proposed algorithm, Joint Adaptation of Transmission power and Bit rate (JATB) algorithm uses modified Dynamic Programming (DP) to search for optimal value of transmission power and bit rate with the aim to increase packet success rate, minimize end-to-end delay and minimize busy time. JATB also uses vehicle density to improve vehicular environment awareness, and adapt transmission power and bit rate accordingly. Adaptability of JATB algorithm is tested with different beacon rates and simulation scenarios. Simulation results show an improvement in transmission efficiency as compared to standard protocol [original algorithm set in VANET standard which has fixed transmission power (20 mW) and fixed bit rate (6Mbps)] and reference journal’s Transmission Power Transmission Range (TPTR) [algorithm from reference journal that adapts transmission power according to transmission range] algorithms.